Pre-purchase information search: too many sources to choose. Issue 3 (8th August 2016) - Broilo, Patricia Liebesny; Espartel, Lélis Balestrin; Basso, Kenny
Abstract : Purpose: Because of the increasing volume of information spread in physical and online environments, a consumer intending to purchase a product or service must choose not only what to buy but also which sources to consult when searching for information that may aid decision-making. This study aims to understand how consumers choose their sources of information in pre-purchase external searches, given the information overproduction scenario. Design/methodology/approach: Using a qualitative approach, data collected through interviews with consumers were analyzed under the technique of content analysis, and the results were synthesized into a framework. Findings: Consumers tend to consider few sources of information, based on a previously built perception of which sources are more or less appropriate for consultation. Choice tends to be based on pre-established evaluation criteria involving the use of heuristics in the form of socialized images regarding those sources. Research limitations/implications: Despite the study's exploratory nature, the proposed framework sheds light into how consumers respond to information overproduction when choosing their sources, providing interesting venues for future investigations. Practical implications: The study identified the possible occurrence of consumer confusion associated with information sources, extending the theoretical understanding of such a concept. Moreover, it revealed the need for managers to consider specific aspects related to the sources to be included in marketing communications. Originality/value: This is the first study to address choice of information sources associated with consumer confusion focusing the offline/online scenario.